Performance Evaluation of a Suspension-Type Dehumidifier with a Heating Module for Smart Greenhouses - Islam, Md Nafiul; Iqbal, Md Zafar; Ali, Mohammod; Jang, Bo-Eun; Chowdhury, Milon; Kabir, Md Shaha Nur; Jang, Seung-Ho; Chung, Sun-Ok (Journal of Biosystems Engineering, 45(3), 2020)
Purpose The management of the temperature and humidity inside greenhouses is essential for optimum crop growth. The temperature and humidity statuses extensively depend on the performance of dehumidifiers and heaters in the greenhouses. The objective of this study was to evaluate the performance of a small-scale suspension-type dehumidifier with a heating module in terms of temperature and humidity changes over time, and monitoring and controlling the status of individual actuating components in summer and winter. Methods The prototype consisted of a dehumidifier, a fan, and a heating module. Twenty-seven temperature and humidity sensor nodes were placed in three layers (top, middle, and bottom) and in three sections (front, center, and rear sides) for monitoring the temperature and humidity statuses. Two additional temperature and humidity sensor nodes were placed in front of the module and outside the greenhouses. An on/off controller was used to manage the temperature and humidity during the operation of the dehumidifier. Results Remote monitoring and controlling was successfully achieved to operate the dehumidifier with a heating module without interruption during the experiments. The time response and change results confirmed the satisfactory performance of the on/off control. The power consumption values varied depending on the status of the actuators. When the dehumidifier, fan, and heater were turned on, the average power consumption values were 556.64 ± 1.94, 125.80 ± 1.26, and 3779.60 ± 2.24 W, respectively. The temperature and humidity showed a considerable amount of spatial and vertical variability, and the temperature and humidity changes were greater in the middle section than in the other sections in both the summer and winter greenhouses. Conclusion The outcomes of the research support the need for small-scale suspension-type dehumidifiers for region-specific temperature and humidity management, and may inform possible improvement of the prototype.